Fashion recommendation system using Fuzzy Analytic Hierarchy Process (FAHP) / Muhammad Hakim Husin - Husin, Muhammad Hakim (2025)
The project aims to address the challenge of enhancing the personalization of fashion recommendations, a task that is becoming increasingly complex due to the vast array of fashion options available online. Many users face difficulties in selecting styles that match their preferences, often resulting in decision fatigue and dissatisfaction. To tackle this problem, the project employs the Fuzzy Analytic Hierarchy Process (FAHP), a multi-criteria decision-making model capable of handling the uncertainty in human decision-making. This methodology is chosen for its ability to provide recommendations by incorporating fuzzy analytic hierarchy process (FAHP) to better interpret and match user preferences.